The Sustainable City...a mechanism to achieve the quality of urban life - Hafidi, Lilia (Journal of Human Sciences, 2022)
This article seeks to tackle the subject of the sustainable city as a tool for attaining quality urban life through examining the reality of cities and the problems they encounter in Algeria;  while highlighting its sustainability strategy and its role in the development of society by meeting its needs and achieving its material and moral comfort while providing a well-groomed and organized environment, working directly to upgrade The basic elements of his urban life, which are social, economic, urban and environmental elements.This was done through a field study, which relied on the descriptive approach, and a cross sample consisting of 178 items, based on an electronic questionnaire containing 30 items, through which the extent to which urban development projects contributed to achieving the quality of urban life for urban residents was reached, which inevitably leads to a high Percentage of their satisfaction with the way they live.